The Tumor-Associated Neutrophils-Related Signatures Predict Prognosis and Indicate Immune Landscape in Colorectal Carcinoma - Ying Wang; Yizhen Zhu; Yuling Zeng; Shuhui Gao; Youcai Tang; Ming Wei (Mediators of Inflammation)
Conclusions: This study comprehensively analyzed the role of TANs in CRC progression and developed a prognostic model based on TANs-related genes, which holds significant potential for predicting prognosis and immunotherapy outcomes in CRC patients.